2008
DOI: 10.3844/ajassp.2008.1013.1018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Parameters Affecting Warping In Radial Forging Process

Abstract: Radial forging is a process in which one or two punches move axially causing a radial flow into a die cavity by means of which a flange is formed. During forging, warping, in which the lower face of thin flange rises from the die face may occur. To better understand the effect of parameters affecting the warping in radial forging a Finite Element analysis was used to simulate the process with isotropic elastic-plastic material model. Parameters such as die corner Radius (r) or shape and ring gap Height (H), on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As a result, the strain homogeneity is improved with the increases of corner radius. Djavanroodi et al [16] have recently shown that the increase of the corner radius Distant from center to surface (A-B) (mm)…”
Section: Effect Of Corner Radiusmentioning
confidence: 99%
“…As a result, the strain homogeneity is improved with the increases of corner radius. Djavanroodi et al [16] have recently shown that the increase of the corner radius Distant from center to surface (A-B) (mm)…”
Section: Effect Of Corner Radiusmentioning
confidence: 99%
“…There are many model checking systems which are developed; the most popular are SMV (McMillan, 1999;Islam et al, 2010), UPPAAL (Bengtsson et al, 1995;El Emary and Al Rabia, 2005), SPIN (Holzmann, 2003) and PRISM (Marta, 2003, Chandren et al, 2010. Each of the model checkers comes in a package with its own input language which has strict notations and features (Bhaduri and Ramesh, 2004;Djavanroodi et al, 2008). The SMV language is used to describe a finite state transition relational model.…”
Section: Introductionmentioning
confidence: 99%